Prevalence of use of tobacco, alcohol consumption and physical activity in the North East region of India. (March 2021) - Oswal, Kunal; Kanodia, Rishav; Kharodia, Neha; Pradhan, Akash; Gupta, Neha; Singh, Ajita; Sethuraman, Lakshman; Venkataramanan, Ramachandran; Caduff, Carlo; Purushotham, Arnie
Highlights: High cancer burden in the Northeast region of India. Limited awareness about risk facotrs and cancer prevention strategy. Engaged in tobacco, alochol use and limited physical activtiy. Focus on multiprogned approach for prevention though Interpersonal skills. Abstract: Background: Cancer patients in the North East Region (NER) of India have poorer survival rates compared with the rest of India. This is due to late stage at presentation related to poor awareness, risk factors such as use of tobacco, alcohol consumption and less physical activity, This study aims to determine the association between socio-demographic characters and use of tobacco, alcohol consumption and physical activity among people in the NER. Methods: A cross-sectional study of 1400 participants was conducted across Assam, Nagaland and Meghalaya in the NER. A questionnaire was developed to study the socio-demographic profile and factors such as use of tobacco, alcohol consumption and physical activity among participants. Multivariate analysis was performed to understand tobacco and alcohol use and physical activity and a logistic regression analysis was performed to understand the association of different independent variables with lifestyle practice. Results: Use of tobacco and alcohol consumption was highest amongst males, 25−44 years age range and middle income group as defined in this study. The main reasons given for quitting tobacco and alcohol were becoming aware of the harmful effects of using tobacco, pressure from family and friends, and noticing a deterioration in health. Over 90 % of tobacco users and consumers of alcohol initiated this between 10–30 years of age. In all, 62 % of participants rarely or never engaged in any physical recreational activity. Conclusion: Patterns of use of tobacco and consumption of alcohol and recreational physical activity undertaken in the NER show a strong relationship with gender, age and household income. Policy implications: The paper finds a close association of different pattern of modifiable habits which are the risk factors for cancer in the Northeast Region. The limited awareness about the risk factors strengthen the case of context specific prevention strategies and constant reinforcement of behavior communication strategies by using multipronged approach.